The Parenting of Single Parents in Forming Discipline for Ibtidaiyah Madrasah Students - Satriawati, Satriawati; Rokhman, Mauhibur; Saputra, Nanda; Anggraini, Sitti; Abou-Samra, Reem (Tafkir: Interdisciplinary Journal of Islamic Education, 2023)
This article is motivated by student discipline records that show promising results. This disciplinary background cannot be separated from how single parents educate students in the family. This condition is certainly not in line with the theory of student discipline, where students with good discipline come from families that are intact and compact in educating their children. This article aims to find out and describe the Single Parent Parenting Pattern in Shaping the Discipline of MI Darussalam Pacet Mojokerto Students and the Causes of Single Parenting Patterns in Shaping the Discipline of MI Darussalam Students Pacet Mojokerto. This article has used a qualitative type with a case study approach centered on one well-disciplined student with divorced parents. The results of this study are 1) Parenting applied by single parents to students using a combination of authoritarian and authoritative parenting. 2) The causal factors are classified into internal and external.